Ultrastructure and regulation of color change in blue spots of leopard coral trout Plectropomus leopardus - Zhao, Nannan; Ge, Xiaoyu; Jiang, Ke; Huang, Jing; Wei, Ke; Sun, Chao; Chen, Shi Xi (Frontiers in Endocrinology, 2022)
The leopard coral trout generally exhibited numerous round, minute blue spots covering its head (about the size of nostril) and body (except ventral side). This is a characteristic that distinguishes them from similar species. Recently, however, we found the leopard coral trout with black spots. Here, the distribution and ultrastructure of chromatophores in the blue and black spots were investigated with light and transmission electron microscopies. The results showed that in the blue spots, two types of chromatophores are present in the dermis, with the light-reflecting iridophores located in the upper layer and the aggregated light-absorbing melanophores in the lower layer. Black spots have a similar chromatophore composition, except that the melanosomes within the melanophores disperse their dendritic processes to encircle the iridophores. Interestingly, after the treatment of forskolin, a potent adenylate cyclase activator, the blue spots on the body surface turned black. On the other hand, using the skin preparations in vitro, the electrical stimulation and norepinephrine treatment returned the spots to blue color again, indicating the sympathetic nerves were involved in regulating the coloration of blue spots. Taken together, our results revealed that the blue spots of the leopard coral trout can change color to black and vice versa, resulting from the differences in the distribution of melanosomes, which enriches our understanding of the body color and color changes of fishes.